Fenomena Kesehatan Remaja Imigran Indonesia dan Remaja Indonesia - Asta Adyani (Jurnal Keperawatan Muhammadiyah, 2022)
Objective: The purpose of this study was to describe the phenomenon of Reproductive Health for Indonesian Immigrant Adolescents and Indonesian AdolescentsMethods: The research was conducted using qualitative methods with a phenomenological approach. The data analysis used is descriptive. Data assessment is carried out based on existing data, and conclusions will be drawn. The existing qualitative data is processed according to the variables included in the research using the induction method. In-depth interviews were carried out during the data collection procedure. The population in this study was all Indonesian immigrant youth and an Indonesian youth. The research sample was 56 female students. Sampling method with purposive sampling. This research was conducted in January 2021.Results: The results showed that most respondents, namely 30 respondents or 53.57%, had a girlfriend. The results showed that 31 respondents, or 55.36% answered that their friends were pregnant before marriage, and 44.64% answered that none of their friends got pregnant before marriage. The results of research related to intentional abortion showed that the majority, namely 45 respondents or 80.36%, stated that none of their friends had abortions. There were 11 respondents or 19.64%, said their friend had an abortion. The program of health service providers has implemented programs related to adolescent reproductive health properly, which are supported by the existence of policies and facilities for health service providers related to adolescent reproductive health. However, the obstacles experienced in implementing the program were time and the lack of optimal assistance specifically for adolescents by health service providers.Conclusion: Most of the respondents already have a girlfriend. Most adolescent courtship styles lead to free sex. Some of the suggestions put forward are the need for supervision and guidance for students from parents and schools and the community both at school and at home; it is necessary to optimize the existence of Adolescent Information and Counseling Centers in Indonesia and Malaysia, which help increase knowledge and counseling about reproductive health and establish cooperation between institutions related to the implementation of counseling for the resilience of adolescent reproductive health and the dangers of deviant sexual behavior.